Bottom trawl surveys show a sharp decline in European eel (Anguilla anguilla) abundance in northern European coastal waters - Svedäng, Henrik (Frontiers in Fish Science, 2025)
Almost 50 years ago, the first signs of population decline in the European eel (Anguilla anguilla) were observed when upstream migration of yellow eel and catches of silver eel decreased in the Baltic Sea. Since then, the decline in recruitment has continued throughout the eel's range, and many indices based on early life stages are now hovering at extremely low levels. Consequently, the European eel is considered critically endangered, which has been linked to overfishing and habitat destruction, including barriers, spread of parasites, contaminants, and climate change. Measurements of European eel escapement are considered difficult to obtain because return sea migrations occur diffusely from all possible coasts, including marine habitats. Currently, the main source of data is the reported commercial landings data, which are subject to several uncertainties. Such uncertainties make evaluating stock status and the efficiency of eel management plans (EMPs) difficult. In this study, data on eel catches are presented from fishery independent international trawl surveys, which often is a more consistent data source than fisheries-dependent data (i.e., tag returns and landing reports from commercial fisheries). The trawl survey data presented here show drastic declines in eel abundance over the last 30–35 years throughout the Baltic Sea, the Kattegat, and the southern North Sea both regardless of size and in the group of larger eels (≥50 cm). This decline in abundance of larger eels calls into question the effectiveness of national EMPs and the future of the European eel.